THE MAIN DIRECTIONS OF IMPROVING THE EFFECTIVENESS OF HUMAN CAPITAL MANAGEMENT IN AGRICULTURE (Journal of Economic Research & Business Administration, 2018)
The authors discussed the main directions of increasing the efficiency of human capital managementin agriculture of Kazakhstan. Human capital plays an important role in the economy, its developmentsolves many socio-economic problems, accelerate innovative development in the country. The growthof quantitative and qualitative parameters of human capital development in agriculture in the moderneconomy, enhancing its competitive advantage possible through effective data management process.Conducted an analysis of employment’ dynamics in agriculture.The main objectives of increasing theefficiency of human capital management in agriculture: smoothing of structural imbalances in the labourmarket, support of young specialists; improved financial incentives for employees; mitigation of theseasonality of work; conducting qualitative personnel work, etc. The authors present a variant of thesystem of socio-economic conditions for effective development of human capital in agriculture, wherethe underlying system is the planning and forecasting of human resource development, and improvingdevelopment effectiveness, utilization and management of human capital in the agricultural sector. Weremade correlation analysis, which revealed that income level significantly affects agricultural productivity,the skill level of employees and average annual wages. The majority of investigated farms belong tothe second group, with incomes from 2000 to 3871,5 thousand tenges, which have high enough productivityand shares of workers in higher skill level in comparison with the third group of farms. Therefore,the authors propose to stimulate the workers of the main production to achieve the efficient functioningin agriculture.